Investigation of a UPR-Related Gene Signature Identifies the Pro-Fibrotic Effects of Thrombospondin-1 by Activating CD47/ROS/Endoplasmic Reticulum Stress Pathway in Lung Fibroblasts - Jun-Hui Zhan; Juan Wei; Lin Liu; Yi-Tong Xu; Hui Ji; Chang-Nan Wang; Yu-Jian Liu; Xiao-Yan Zhu (Antioxidants, 2023)
Unfolded protein response (UPR) signaling and endoplasmic reticulum (ER) stress have been linked to pulmonary fibrosis. However, the relationship between UPR status and pulmonary function and prognosis in idiopathic pulmonary fibrosis (IPF) patients remains largely unknown. Through a series of bioinformatics analyses, we established a correlation between UPR status and pulmonary function in IPF patients. Furthermore, thrombospondin-1 (TSP-1) was identified as a potential biomarker for prognostic evaluation in IPF patients. By utilizing both bulk RNA profiling and single-cell RNA sequencing data, we demonstrated the upregulation of TSP-1 in lung fibroblasts during pulmonary fibrosis. Gene set enrichment analysis (GSEA) results indicated a positive association between TSP-1 expression and gene sets related to the reactive oxygen species (ROS) pathway in lung fibroblasts. TSP-1 overexpression alone induced mild ER stress and pulmonary fibrosis, and it even exacerbated bleomycin-induced ER stress and pulmonary fibrosis. Mechanistically, TSP-1 promoted ER stress and fibroblast activation through CD47-dependent ROS production. Treatment with either TSP-1 inhibitor or CD47 inhibitor significantly attenuated BLM-induced ER stress and pulmonary fibrosis. Collectively, these findings suggest that the elevation of TSP-1 during pulmonary fibrosis is not merely a biomarker but likely plays a pathogenic role in the fibrotic changes in the lung.